Efektivitas Penggunaan E-Filing Dalam Pelaporan SPT Tahunan Wajib Pajak Orang Pribadi Di Kota Manado - Ponto, Rosalini Thavinia; Karamoy, Herman; kindangen, wulan (Universitas Sam Ratulangi, 2022)
ABSTRACTTax reporting is a manifestation of state obligations and the participation of Taxpayers to directly and jointly carry out tax obligations to finance the State and national development. This study aims to obtain evidence regarding the effectiveness of the use of e-filling in reporting the Annual Tax Return of Individual Taxpayers, as well as to find out the ease, security and confidentiality of reporting using e-filing. The analytical method used in this research is descriptive quantitative analysis method, based on the validity and reliability test data to obtain information by collecting data, then compiled, and the conclusion is drawn from the data collected through the interview process and questionnaires on the object of research with theory. and previous research, and the type of research used is quantitative. The results of this study indicate that many taxpayers find it easy to report SPT with e-filing and the security and confidentiality of e-filing is very guaranteed, and the implementation of e-filing in Manado City has been going well, this can be seen from the Annual SPT report. starting from 2016-2020 with the results of calculations using the effectiveness ratio formula, namely from 100%, 73.7% of individual taxpayers have reported their SPT using e-filling from 2016-2020, which continues to increase so that it is consideredeffective. Keywords : Effectiveness, Electronic Filing, Tax Return